2019
DOI: 10.3390/app9071459
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Machine Learning Regression Algorithms for Cotton Leaf Area Index Retrieval Using Sentinel-2 Spectral Bands

Abstract: Leaf area index (LAI) is a crucial crop biophysical parameter that has been widely used in a variety of fields. Five state-of-the-art machine learning regression algorithms (MLRAs), namely, artificial neural network (ANN), support vector regression (SVR), Gaussian process regression (GPR), random forest (RF) and gradient boosting regression tree (GBRT), have been used in the retrieval of cotton LAI with Sentinel-2 spectral bands. The performances of the five machine learning models are compared for better appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…In contrast to the findings of Richter et al [ 22 ] and Verrelst et al [ 39 ], introducing additional bands did not enhance the GAI-prediction ( Table 3 ). This could be examined further, considering the full spectrum of Sentinel-2 bands and calibration methods—for example, machine learning regression algorithms [ 12 , 42 ]. However, other studies already demonstrated good results applying simple VI-approaches to Sentinel-2 data [ 11 , 22 ] and it should be kept in mind that a simple but still relative well working VI-approach is easier to communicate and has the advantage of lower download- and processing time [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the findings of Richter et al [ 22 ] and Verrelst et al [ 39 ], introducing additional bands did not enhance the GAI-prediction ( Table 3 ). This could be examined further, considering the full spectrum of Sentinel-2 bands and calibration methods—for example, machine learning regression algorithms [ 12 , 42 ]. However, other studies already demonstrated good results applying simple VI-approaches to Sentinel-2 data [ 11 , 22 ] and it should be kept in mind that a simple but still relative well working VI-approach is easier to communicate and has the advantage of lower download- and processing time [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the analysis revealed several deficiencies of the NIR/RE-model, raising the topics of temporal and spatial resolution. Apparently, the frequent statement that the GAI-course over the season can be well mapped with Sentinel-2 data [ 3 , 11 , 12 , 21 , 29 , 37 , 40 , 41 , 42 , 43 , 44 , 45 ] is based on large differences and continuously increasing GAI-values between different sampling dates. Yet, the Sentinel-2 based single-date GAI-estimations are at some dates systematically biased and the true GAI-variation is in most cases considerably underestimated ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, to validate the performance of the ML models, the dataset was split in 80% (n = 3940) for model training, and 20% (n = 980) for model testing, so we could investigate the model generalization ability [32]. To eliminate the dimensional differences of the data and also improve the prediction ability of the models, we used the StandardScaler method from the Scikit-Learn package, which standardizes features by removing the mean and scaling to unit…”
Section: Datasetsmentioning
confidence: 99%
“…Mao et al [17] in their paper entitled "Comparison of Machine Learning Regression Algorithms for Cotton Leaf Area Index Retrieval Using Sentinel-2 Spectral Bands" compared the algorithm performance of five advanced machine learning regression algorithms, including ANN, support vector regression (SVR), Gaussian process regression (GPR), RF, and gradient boosting regression tree (GBRT), to retrieve cotton leaf area index (LAI) in a relatively comprehensive manner. Although the five models showed different performance, all of the models showed a potential for cotton LAI retrieval.…”
Section: Machine Learning Techniques and Their Applicationsmentioning
confidence: 99%